2004
DOI: 10.1002/ana.20104
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system abnormalities in asymptomatic young patients with Sβ‐thalassemia

Abstract: Twenty-one children and young adults with sickle/beta-thalassemia without overt stroke were examined with magnetic resonance imaging and angiography (MRA), transcranial Doppler (TCD), visual (VEP) and median nerve somatosensory (SEP)-evoked potential recordings, and neuropsychological testing (Wechsler Intelligence Scale [WISC-III]). Eight (38%) had silent infarction in the parietooccipital cortex, deep white matter, or basal ganglia, including two of three with previous seizures. Of 17 undergoing TCD, none ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
3
27
2
1
Order By: Relevance
“…15 Similar observations were reported for an unselected cohort of 132 children with SCA in Créteil, France undergoing brain MRI as part of routine medical care 2 and in other studies. 4,5,17,18 SCI in SCA are typically smaller in size compared with overt strokes. In the CSSCD participants, 83% of the children with overt strokes, but only 16% of those with SCI, had lesions that were at least 1.5 cm.…”
Section: Clinical Significance Of Scismentioning
confidence: 99%
See 1 more Smart Citation
“…15 Similar observations were reported for an unselected cohort of 132 children with SCA in Créteil, France undergoing brain MRI as part of routine medical care 2 and in other studies. 4,5,17,18 SCI in SCA are typically smaller in size compared with overt strokes. In the CSSCD participants, 83% of the children with overt strokes, but only 16% of those with SCI, had lesions that were at least 1.5 cm.…”
Section: Clinical Significance Of Scismentioning
confidence: 99%
“…15 SCI is most common in patients with hemoglobin SS but may also be identified in individuals with heterozygous genotypes including sickle ␤-thalassemia and hemoglobin SC (HbSC) disease. Approximately 3% to 38% of patients with sickle ␤-thalassemia, 17,18,20,21 and 5% to 31% of those with HbSC disease, 15,22 will have SCI. However, limited sample size allows no significant inferences about the rate of progression or potential benefit of therapy.…”
Section: Clinical Significance Of Scismentioning
confidence: 99%
“…21,22 Although the etiology of SCI is unknown, the consistent finding that anemia is a risk factor strongly implicates cerebral hemodynamic insufficiency as a central component. All patients with chronic anemia have a compensatory mechanism in the brain (auto-regulation) that occurs with vasodilation of the cerebral vasculature and manifests initially as increased cerebral blood flow.…”
Section: Risk Factors For Silent Infarcts In Sca 3687mentioning
confidence: 99%
“…Few studies in patients with HbS-b thalassemia have been reported and the results are inconclusive [21][22][23][24]. The effectiveness of HU for the prevention of silent cerebral infarction has not been reported.…”
Section: Introductionmentioning
confidence: 99%